Augmented Reality dalam Pengenalan Koleksi Museum Karst Indonesia dalam Aplikasi Mobile - Ariadanu, Bian Kusharyanto; Zakariyah, Muhammad (Teknik Informatika Universitas Pamulang, 2023)
Museums serve as guardians of historical, cultural artifacts, and research outcomes. Yet, sharing collections with the public is vital to fostering appreciation for a museum's legacy and expanding knowledge. Regrettably, the Museum Karst Indonesia's collection introduction relies solely on text and images, lacking allure. This study aims to revolutionize this by employing Augmented Reality (AR) for a more captivating display. Through the AR application, visitors can explore the collection interactively, featuring 3D objects and real-time audio explanations drawn from the museum's Application Programming Interface (API). Employing the Multimedia Development Life Cycle (MDLC), this research rigorously tests the application using blackbox, distance, and lighting methods, showing its effectiveness within these parameters. Users engaging with markers should maintain a distance of 5 to 70 cm for accurate detection under suitable lighting conditions. AR's implementation anticipates enhancing the Museum Karst Indonesia's appeal as an educational tourist spot, enriching visitor experiences, and deepening comprehension of Indonesia's natural wealth.